Livelihood Strategies of Porang Farming Households in Bontolempangan Village, Bontolempangan Sub-district, Gowa Regency, Indonesia - Nurwahidah Nurwahidah; Jumiati Jumiati; Nadir Nadir; Amruddin Amruddin; Firmansyah Firmansyah (PT FORMOSA CENDEKIA GLOBAL, 2026)
Porang cultivation is characterized by delayed economic returns and high exposure to market and climate uncertainties, requiring farming households to adopt adaptive livelihood strategies. Understanding how households manage income volatility and welfare stability in such conditions is critical for rural development policy. This study examines how porang-farming households in Bontolempangang Village construct and organize their livelihood strategies to manage risk, stabilize income, and reduce vulnerability. Using a qualitative case-study approach, the study analyzes household livelihood structures, income sources, and adaptive strategies across on-farm, off-farm, and non-farm sectors. Data were examined through a sustainable livelihoods framework to identify patterns of diversification and risk management. The findings reveal that livelihood patterns are multi-stranded and risk-oriented. Households adopt adaptive strategies grounded in a combination of multiple income sources, including: (i) agricultural livelihood engineering (intensification and extensification), (ii) occupational and institutional diversification, and (iii) spatial strategies such as temporary/circular migration and remittances. Agriculture remains the primary livelihood base, with maize functioning as a short-cycle cash-flow bridge, rice as a subsistence anchor with marketable surplus, and cattle raising as a precautionary liquid asset. These strategies are reinforced by off-farm bamboo crafts and non-farm income (e.g., construction work and village institutional honoraria), which improve cash-flow stability and facilitate consumption smoothing. Porang-farming households construct resilient livelihood systems through strategic diversification and cross-sectoral income buffering. The integration of agricultural and non-agricultural activities serves as an adaptive mechanism to manage delayed returns and mitigate economic vulnerability under uncertain market and environmental conditions.